What Is the Impact of the Flipping the Classroom Instructional e-Learning Model on Teachers - Lut De Jaegher (Voprosy obrazovaniya / Educational Studies Moscow, 2020)
Flipping the classroom is an instructional model in which students learn basic subject knowledge prior to the face-to-face class moment, where they can have active learning experiences with their peers and teachers. Research revealed the positive effects for students, who can learn at their own pace, reach up to the highest level of the thinking skills of Bloom’s taxonomy, exercise and improve their collaboration, communication and ICT skills. Where most of the research concentrates on the learning effects for the students, this paper presents the results of recent European research on the impact for teachers. Setting up a learning path for flipped classroom, is a big challenge. Together with 7 European partners from Belgium, Italy, Bulgaria, Slovenia, Poland and the Netherlands, we did research on how students and teachers perceive the implementation of the flipped classroom model in their teaching and how challenging the integration of technology in their lessons is. We also asked about their perceptions: are the benefits worth the efforts, is the flipped classroom model improving their teaching skills and what are their needs and requirements to get succeed? We started by getting the teachers a flipped classroom instruction to learn the method, combined with a face-to-face training in Belgium, where they were supported to create a flipped classroom learning path for their own subjects and classes. Then, they implemented the method in their institutions for adult and higher education. The surveys were conducted after this try out, in all of the 7 European participating countries. The research results of the surveys will be presented and used to make recommendations that increase the chance of a successful implementation of the flipped classroom method. These recommendations were tested and evaluated during flipped classroom trainings at teacher training departments in Belgium and Vietnam. The qualitative test results will also be presented in this paper.